Letter to Jane Tolmach from Joyce Fadem - Joyce Fadem:::::: (1967)
A letter from the Democratic State Central Committee that invites Jane Tolmach to help plan a two-day 1968 campaign kick-off conference to be held in Fresno on January 13–14, 1968. State Chairman Charles Warren asks her to meet with him and others to develop the format for the conference, drawing on their combined experience to create an effective workshop for Democratic leaders statewide. The first planning meeting is scheduled for September 17, 1967, in Los Angeles, and she is asked to RSVP if she can attend.